Delusional Misidentification Syndromes and Dementia: A Border Zone Between Neurology and Psychiatry. (November 2013) - Cipriani, Gabriele; Vedovello, Marcella; Ulivi, Martina; Lucetti, Claudio; Di Fiorino, Andrea; Nuti, Angelo
The delusional misidentification syndromes (DMSs) are psychopathologic phenomena in which a patient consistently misidentifies persons, places, objects, or events. Although often described in relation to psychotic states including schzofrenia, it is, nevertheless, widely considered that these syndromes have an anatomical basis because of their frequent association with organic brain disease; studies have pointed to the presence of identifiable lesions, especially in the right frontal lobe and adjacent regions, in a considerable proportion of patients. The purpose of this article is to examine the phenomenon in people with dementia. We searched the electronic databases for original research and review articles on DMS in patients with dementia using the search terms "Delusional Misidentification Syndrome, Capgras syndrome, Fregoli syndrome, reduplicative paramnesia, and dementia." The DMSs are a frequent problem in dementia. The violence and dangerousness in patients with dementia having these syndromes are well documented, and forensic aspects are highlighted. Pathogenetic viewpoint and management are considered.